PENGUKURAN KUALITAS WEBSITE BADAN NASIONAL PENANGGULANGAN BENCANA MENGGUNAKAN METODE WEBQUAL 4.0 - Fathur Rohman; Didik Kurniawan (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
This research is based on the extent to which the National Disaster Management Agency website (BNPB) can be useful and accepted by internet users, therefore it is necessary to hold an assessment to measure the quality of the website is well received or not, so the quality of the website based on the user perception Is an important thing to know and be used as feedback to the provider. And can optimize the features and menus contained therein in order to accommodate the needs of users. The author uses the WebQual 4.0 method of usability, information quality, interaction quality, and overall impression. The result, 51.9% user satisfaction is supported by these three factors and the hypothesis in this study is accepted which is shown by correlation technique and multiple linear regression.